Higher in-utero exposure to greenspace can reduce the prevalence of low birth weight in India - Gautam Saw; Joe Van Buskirk; Sagnik Dey; Luke D Knibbs (Environmental Research Letters, 2025)
An emerging body of evidence suggests that exposure to residential greenspace may provide reproductive health benefits to mothers during pregnancy by promoting physical activity and reducing exposure to environmental risks. Here, we addressed this evidence gap in India and assessed the association between residential greenspace and the prevalence of low birth weight (LBW) (birth weight ⩽2500 g) among Indian mothers. We analyzed health and demographic data from India’s National Family and Health Survey conducted between 2015–16 and 2019–21. Greenspace exposure was quantified using high-resolution moderate resolution imaging spectroradiometer-derived enhanced vegetation index (EVI) data with a 30–days temporal resolution. Multivariable binomial logistic regression models were employed, adjusting for maternal demographics, lifestyle behaviors, socioeconomic status, household characteristics, and exposure to fine particulate matter (PM _2.5 ). Among 38 358 participants, 13 677 (35.6%) had LBW. We found a protective association between EVI and the odds of LBW, with an odds ratio (OR) of 0.99 (95% CI: 0.95–1.03) after controlling for covariates. When stratified by PM _2.5 exposure levels, the protective effect of EVI was strongest in areas with low PM _2.5 concentrations (OR = 0.92; 95% CI: 0.85–1.00), corresponding to an 8% reduction in the odds of LBW. In areas with medium-high exposure, the effect was attenuated (OR = 0.97; 95% CI: 0.90–1.06), while in high exposure areas, the association reversed, with EVI linked to a 23% increase in LBW odds (OR = 1.23; 95% CI: 1.13–1.34). The protective effect was found in urban areas rather than in rural areas and in economically affluent households. Our results suggest that increasing access to greenspace can serve as an adaptive measure to reduce the prevalence of LBW. Further cohort studies are recommended to ascertain the underlying mechanisms.